Entropy solution for a nonlinear degenerate parabolic problem in weighted Sobolev space via Rothe's time-discretization approach - Abdelali Sabri; Ahmed Jamea (Boletim da Sociedade Paranaense de Matemática, 2022)
In this paper, we prove the existence and uniqueness results of an entropy solution to a class of nonlinear degenerate parabolic problem with Dirichlet-type boundary condition and L1 data. The main tool used here is the Rothe's time-discretization approach combined with the theory of weighted Sobolev spaces.